Pandemic Preparedness of Healthcare Team and Healthcare Facilities in La Union (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
In the last several decades, pandemic preparedness has not been this urgently and widely needed. Amu & Nyarko (2016) states that healthcare professionals' preparedness for emergencies is indispensable in quality health care. Staff and healthcare facilities play an essential role in emergency preparedness and response efforts for all incidents. Healthcare services must be readily available during an emergency or disaster to meet the demand surge (premiersafetyinstitute.org). The Corona Virus disease2019, discovered in Wuhan, China, in 2019, is a new strain of the virus and an infectious disease caused by severe acute respiratory syndrome (covid19.gov.ph). Descriptive-developmental design 58 or 24.68% are aged 31 to 35 years old, 82 or 34.89% are nurses, 175 or 74.47% are college graduate, 111 or 47.23% are 5 years below in service, and 164 or 69.79% has 1 to 3 recent training. The level of preparedness of the healthcare team during a pandemic along the areas of Knowledge, Skills, Attitude, and Working Relations are categorized as Very Adequate. The level of preparedness of healthcare facilities in all areas is categorized as Very Adequate. Position and Highest Educational Attainment have a significant relationship to the level of preparedness of the healthcare team. The profile of the respondents has no significant relationship to the level of preparedness of the healthcare facility. The level of preparedness of the health care team is significantly related to the level of preparedness of healthcare facilities. Nurses are needed in every part of healthcare. The highest educational attainment is very important for professional preparedness. Training is important to employees to improve their productivity and performance. When you have a good attitude you can easily work together with the team, when you know, you have the skills to perform it. If healthcare teams and facilities are adequate, they are well-prepared and equipped during the pandemic.
Keywords: Pandemic Preparedness Program, Healthcare Team, Healthcare Facility